Enhancing English Language Instruction In Medical Institutes: Insights From Professional Practice (Eurasian Research Bulletin, 2024)
This abstract is derived from practical experience and aims at emphasizing the distinctive features of teaching English in a medical university. The study investigates the intricate methods, challenges, and specific techniques essential in teaching English language skills within the context of medical education. The research aims to identify efficient educational strategies that meet the particular demands and requirements of students in a medical university setting by leveraging real-world experiences. Through applying knowledge and practical implications from authentic work settings, this thesis explores the unique facets and effective teaching techniques of English in the context of a medical university. It seeks to propose innovative approaches, tailored curriculum designs, and pedagogical methods that optimize the language learning process for medical students, ensuring their proficiency in English communication skills while navigating the complexities of the healthcare domain. This study does so by examining the intersection of language education and the medical profession.